A novel approach in the prevention of mastitis: electrical teat dipping - Risvanli, Ali; Safak, Tarik; Yilmaz, Oznur; Yuksel, Burak; Saat, Nevzat; Tanyeri, Burak (Cambridge Univ Press, 2022)
Teat dipping is widely used in dairy cattle, especially to protect against contagious mastitis. Here we determine the effect of the device called 'Electrical Teat Dipping' (ETD), which was developed by combining teat dipping application and electrical field stimulation technique on teats. For this purpose, the front teats of 100 Holstein breed milking cows were evaluated in two groups, with ETD being applied once to the left front teat of these cows, and conventional teat dipping (CTD) being applied once to the right front teat, both after milking. Ultrasonographic measurements of the teats were made before milking and after teat dipping. We found that the width of the teat canal (1.88 +/- 0.07 mm) in the teat using ETD was narrower after the application compared to those with CTD (2.28 +/- 0.05 mm). Based on our findings, we conclude that the effects of ETD on the teat are very positive and can potentially be used as a new approach in the preventative control of mastitis in cows.
Keywords: Electrical teat dipping; ultrasonography